3(x+2)+3x+1=2(x-1)-7

Simple and best practice solution for 3(x+2)+3x+1=2(x-1)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)+3x+1=2(x-1)-7 equation:


Simplifying
3(x + 2) + 3x + 1 = 2(x + -1) + -7

Reorder the terms:
3(2 + x) + 3x + 1 = 2(x + -1) + -7
(2 * 3 + x * 3) + 3x + 1 = 2(x + -1) + -7
(6 + 3x) + 3x + 1 = 2(x + -1) + -7

Reorder the terms:
6 + 1 + 3x + 3x = 2(x + -1) + -7

Combine like terms: 6 + 1 = 7
7 + 3x + 3x = 2(x + -1) + -7

Combine like terms: 3x + 3x = 6x
7 + 6x = 2(x + -1) + -7

Reorder the terms:
7 + 6x = 2(-1 + x) + -7
7 + 6x = (-1 * 2 + x * 2) + -7
7 + 6x = (-2 + 2x) + -7

Reorder the terms:
7 + 6x = -2 + -7 + 2x

Combine like terms: -2 + -7 = -9
7 + 6x = -9 + 2x

Solving
7 + 6x = -9 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
7 + 6x + -2x = -9 + 2x + -2x

Combine like terms: 6x + -2x = 4x
7 + 4x = -9 + 2x + -2x

Combine like terms: 2x + -2x = 0
7 + 4x = -9 + 0
7 + 4x = -9

Add '-7' to each side of the equation.
7 + -7 + 4x = -9 + -7

Combine like terms: 7 + -7 = 0
0 + 4x = -9 + -7
4x = -9 + -7

Combine like terms: -9 + -7 = -16
4x = -16

Divide each side by '4'.
x = -4

Simplifying
x = -4

See similar equations:

| 11/28=4/x | | 12x^3-3x^2=0 | | 3.5/x=11/28 | | 55x-12=x-24 | | 59+1.75x=39.99+2.50x | | x(1M)+(-2N)=0 | | 2/3x2-5= | | 3p+6=78 | | 2/3x-5=-2 | | C(t)=2x+180 | | 5x-5y+7a= | | 3=-3/2(x+6) | | Ic(t)=2x+180 | | 16=4(2x+1) | | x-1/2=1/4 | | y^1/7 | | -9=x+20 | | 14=s-61 | | k/-4=3 | | q+5=8(q+7) | | -20=-2+3v | | 6a^2+4a=-11 | | 25-6x=19-5x | | 6m^2+13=5 | | .05x/259y=5550 | | .05x*259y=5550 | | 4x+28=10 | | 18=4w+2 | | .40x+1.25y=150 | | sinx+-1cosx+-1tanx=-1 | | 3y+4x-Y-2x-5y= | | 3(-6+9)+10x=1 |

Equations solver categories